Computational Flow Dynamic Simulation of Micro Flow Field Characteristics Drainage Device Used in the Process of Oil-Water Separation. (4th July 2017) - Jin, Guangya; Liu, Zhijian
Abstract : Aqueous crude oil often contains large amounts of produced water and heavy sediment, which seriously threats the safety of crude oil storage and transportation. Therefore, the proper design of crude oil tank drainage device is prerequisite for efficient purification of aqueous crude oil. In this work, the composition and physicochemical properties of crude oil samples were tested under the actual conditions encountered. Based on these data, an appropriate crude oil tank drainage device was developed using the principle of floating ball and multiphase flow. In addition, the flow field characteristics in the device were simulated and the contours and streamtraces of velocity magnitude at different nine moments were obtained. Meanwhile, the improvement of flow field characteristics after the addition of grids in crude oil tank drainage device was validated. These findings provide insights into the development of effective selection methods and serve as important references for oil-water separation process.